Ordinary's Power to Dispense: Canon 1125 - Robitaille, Lynda (Roman replies and CLSA advisory opinions 1997, 1997)
Recently it was reported that Archbishop Herranz commented that the local ordinary competent to grant dispensations or permissions for mixed marriages is the local ordinary of the Catholic party only. I was surprised to see this, since I had always judged that the local ordinary of the place where the wedding is to be celebrated was also competent to grant the dispensation. For example, as chancellor of the diocese, I receive requests for dispensations when the non-Catholic bride is from our diocese and the Catholic groom is from another diocese. The wedding is being planned here, and the couple is undertaking marriage preparation here. I have always granted the dispensation or the permission, as necessary. I have based my judgment on canon 91, that is, that one who possesses the power to dispense can exercise it for travelers actually present in his territory. My theory has been that the dispensation is for the day of the wedding, when the Catholic groom in the above example is a traveler present in this diocese. Would you care to comment?